The role of hypoxia in intestinal inflammation - Shah, Yatrik M. (Mol Cell Pediatr, 2016)
Inflammatory bowel disease (IBD) is a chronic relapsing inflammatory disease of the intestine. IBD is a multifactorial disorder, and IBD-associated genes are critical in innate immune response, inflammatory response, autophagy, and epithelial barrier integrity. Moreover, epithelial oxygen tension plays a critical role in intestinal inflammation and resolution in IBD. The intestines have a dynamic and rapid fluctuation in cellular oxygen tension, which is dysregulated in IBD. Intestinal epithelial cells have a steep oxygen gradient where the tips of the villi are hypoxic and the oxygenation increases at the base of the villi. IBD results in heightened hypoxia throughout the mucosa. Hypoxia signals through a well-conserved family of transcription factors, where hypoxia-inducible factor (HIF)-1α and HIF-2α are essential in maintaining intestinal homeostasis. In inflamed mucosa, HIF-1α increases barrier protective genes, elicits protective innate immune responses, and activates an antimicrobial response through the increase in β-defensins. HIF-2α is essential in maintaining an epithelial-elicited inflammatory response and the regenerative and proliferative capacity of the intestine following an acute injury. HIF-1α activation in colitis leads to a protective response, whereas chronic activation of HIF-2α increases the pro-inflammatory response, intestinal injury, and cancer. In this mini-review, we detail the role of HIF-1α and HIF-2α in intestinal inflammation and injury and therapeutic implications of targeting HIF signaling in IBD.